Group Peer Disagreement. (11th September 2014) - Carter, J. Adam
Abstract: A popular view in mainstream social epistemology maintains that, in the face of a revealed peer disagreement over p, neither party should remain just as confident vis‐a‐vis p as she initially was. This 'conciliatory' insight has been defended with regard to individual epistemic peers. However, to the extent that (non‐summativist) groups are candidates for group knowledge and beliefs, we should expect groups (no less than individuals) to be in the market for disagreements. The aim here will be to carve out and explore an extension of the conciliatory insight from individual peer disagreement to group peer disagreement ; in doing so, I'll raise and address three key problems that face any plausible defence of such a constraint.